KOMUNIKASI LINGKUNGAN BANK SAMPAH TUAN DI BANGARNA DALAM MENGAJAK MASYARAKAT PEDULI LINGKUNGAN MELALUI KEGIATAN MENABUNG SAMPAH DI PEKANBARU - Annisa, Dwi Ayu; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Tuan Di Bangarna rubbish bank (TDB) is one of non-government rubbish banks in Pekanbaru City which has been operating since 2018. The TDB rubbish bank is a dry waste management system that involves the public to play an active role as a customer by collecting, sorting and distributing rubbish to the market to be converted into money so that it will has economic value and benefits to the community. As a business entity that operates as a rubbish bank itself is active in educating new knowledge about waste and fostering a sense of responsibility to protect the environment for the community. The purpose of this research was to determine the forms of environmental communication, environmental communication media and the environmental communication barriers of the Tuan Di Bangarna rubbish bank in inviting people to care about the environment through saving activities in Pekanbaru.This study used qualitative research methods. The research informants totaling of nine people according to the criteria selected using a purposive technique. Data collection techniques consist of interviews, observation and documentation. While the data analysis technique uses descriptive analysis according to Miles and Huberman. The data validity checking technique uses an extension of participation and triangulation.The result of this study indicate that environmental communication conducted by the TDB rubbish bank implements a form of interpersonal communication, group communication, public communication and mass media communication. TDB rubbish bank also uses communication media in printed media in the form of banners and brochures, visual media using photos and images, audio media in the form of telephone and has its own official jingle, and audio visual media using internet media such as websites and social media. The barriers experienced by TDB in carrying out its environmental communication activities are in the form of obstacles from the delivery process, physical barriers, semantic barriers, social barriers and other barriers in the form of barriers in procedural and time barriers. Keyword: Environmental Communication, Rubbish Bank, Environment Care